Memahami Hubungan Teori Psikoanalisis dan Teori Pengembangan Moral terhadap Terjadinya Suatu Kejahatan di Masyarakat - Febrina Hertika Rani; Dea Justicia Ardha; Heni Marlina (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Crime is a complex phenomenon that can be understood from different sides. Thus, it is not easy to understand the crime itself. Until now, the science of criminology has developed. In criminology, there are many theories to understand crime. In the modern era, criminology is defined as a science that studies and discusses about crime and human behavior deviations both as a social phenomenon or psychology. Therefore, the legal world requires other disciplines that are able to explain each deviation, its relation to behavior, as well as certain psychological situations that motivate criminal behavior. The problem in this research is what is the correlation between psychoanalytic theory and moral development theory on the occurrence of a crime in society? This research uses normative research. Psychoanalytic theory of criminality links delinquent and criminal behavior with a "conscience" that either this is so controlling that it causes feelings of guilt or he is so weak that he cannot control the individual's urges, and for a needs that must be met immediately. A person who performs forbidden behavior because his conscience, or superego is so weak and imperfect that his ego is unable to control the impulses of the id (a part of the personality that contains strong desires and urges to be satisfied and fulfilled). And in the theory of moral development, it is actually a moral understanding of right and wrong that has been instilled since childhood. However, if moral understanding is lacking and the superego is not fully developed, as a result, children can grow up to be individuals who are less able to control the impulses of the Id, and are willing to do anything to achieve what they need. According to this view, crime is not the result of a criminal personality, but of ego weakness. The ego that is not able to bridge the needs of the superego and the id will be weak and make humans vulnerable to deviations. Moral is defined by psychologists as an attitude and belief having by a person that helps to decide what is right and wrong. As Piaget said and later developed by Kohlberg, prove that moral growth is a process of moral development which is a process of forming cognitive structures, to show that moral development is related to cognitive structures. This tradition is based on the assumption that an individual's moral behavior (in terms of what is considered as right and wrong) in some related to their moral (Blasi, 1980) and thus there are a number of choices involved in the decision to act out that moral behavior.